Philosophico-worldviewing aspects of the Ukrainian legal systems. The phenomenon of Pylyp Orlyk - Bychko, Ada (Actual Problems of Mind, 2017)
The paper presents an analysis of the system of legal ideas elaborated in Ukraine from XIII to XVIII cc. The author claims that a thorough investigation of the Pylyp Orlyk’s Constitution as the top-stone of the legal thought in Ukraine will promote the development of Ukrainian national selfconsciousness.